The Effect of Multiple-use of Polystyrene Cups on Styrene Monomer Migration - Siti Nur Hidayah Binti Mat Salleh, Siti Nur Hidayah (Universiti Teknologi Petronas, 2008)
The study has highlighted the negative effect of using PS cup repetitively especially in the presence of fatty medium. The effect may not be as bad if the cup contained only aqueous medium.